The role of social media to promote a culture of values and sustainable development in the Asir region - Abu Malih, Adel Mohammed (Journal of Humanities & Social Sciences, 2023)
The aim of conducting the study is to know the effective role of social media to build and promote sustainable development in the Asir region from the point of view of students of King Khalid University, College of Pharmacy, and students of Bisha University, College of Science. The descriptive method was used to suit this study. The total number of students was one hundred and fifty students as a study sample. The researcher used a number of statistical methods to obtain the results of the study, which are the arithmetic means, standard deviations and one-way analysis of variance. The results obtained indicate that social media in promoting the culture of sustainable development from the point of view of students from King Khalid University and the University of Bisha in the field of health, consumer and environmental awareness were moderate. The results of the obtained study also showed that both students from King Khalid University and Bisha University showed that there is no difference in their views on the effective role of social media to promote a culture of sustainable development in general, and the field of health, consumer and environmental awareness in particular. In conclusion, the research reached a number of recommendations, the most prominent of which is the need to activate the role of educational institutions, ministries and government agencies in promoting a culture of sustainable development by planning, implementing and evaluating several targeted programs related to sustainable development and its importance, as well as the importance of choosing purposeful topics that touch the needs of society regarding sustainable development. Especially in the health, consumer and environmental fields, and the publications should be attractive to ensure follow-up.